Respon Pertumbuhan Bibit Kopi Robusta (Coffea Canephora L.) Terhadap Pemberian Berbagai Konsentrasi Pupuk Cair Hayati - Junaedi Junaedi; Syahruni Thamrin; Suriyadi Suriyadi (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2019)
The study aimed to determine the use of biological liquid fertilizer on the growth of robusta coffee plants. Conducted at the Experimental Garden Department of Plantation Plant Cultivation, Pangkajene and Islands State Polytechnic, which lasted for 3 (three) months. The study used a Randomized Block Design (RBD) with no setting (P0), concentration of 100 ml (P1), concentration of 150 ml (P2), and concentration of 200 ml (P3). Based on the experimental results obtained, it can be concluded that the contribution of biological liquid fertilizer gives different changes to the growth of robusta coffee plant seeds that have been developed for 3 months. The application of fertilizer with a concentration of 200 ml resulted in the growth of the average plant height and stem diameter the best, namely the average plant height of 6.25 cm and the average stem diameter increase of 0.13 cm. While giving the concentration of 100 ml produces the highest average number of leaf growth, namely 7 strands.